Elite football teams that do not have a winter break lose on average 303 player-days more per season to injuries than those teams that do: a comparison among 35 professional European teams - Ekstrand, J.; Spreco, A.; Davison, M. (British Journal of Sports Medicine, 2019)
Objective: To compare injury rates among professional men`s football teams that have a winter break in their league season schedule with corresponding rates in teams that do not.Methods 56 football teams from 15 European countries were prospectively followed for seven seasons (2010/2011-2016/2017)—a total of 155 team-seasons. Individual training, match exposure and time-loss injuries were registered. Four different injury rates were analysed over four periods within the season, and linear regression was performed on team-level data to analyse the effect of winter break on each of the injury rates. Crude analyses and analyses adjusted for climatic region were performed. Results: 9660 injuries were reported during 1 447 011 exposure hours. English teams had no winter break scheduled in the season calendar: the other European teams had a mean winter break scheduled for 10.0 days. Teams without a winter break lost on average 303 days more per season due to injuries than teams with a winter break during the whole season (p<0.001). The results were similar across the three periods August-December (p=0.013), January-March (p<0.001) and April-May (p=0.050). Teams without a winter break also had a higher incidence of severe injuries than teams with a winter break during the whole season (2.1 severe injuries more per season for teams without a winter break, p=0.002), as well as during the period January-March (p=0.003). A winter break was not associated with higher team training attendance or team match availability. Climatic region was also associated with injury rates. Conclusions: The absence of a scheduled winter break was associated with a higher injury burden, both before and during the two periods following the time that many European teams take a winter break. Teams without a winter break (English clubs) had a higher incidence of severe injuries following the time of the year that other teams (other European clubs) had their scheduled break.